Longitudinal evidence of entrepreneurial behaviour in a blockchain-based decentralized autonomous organization: Case study of the Nano cryptocurrency - Alexander Poeschl (Entrepreneurial Business and Economics Review (EBER), 2023)
Objective: The article aims to investigate how entrepreneurial behaviour among members of decentralized autonomous organizations (DAO) changes over time. Decentralized autonomous organizations allow for the creation of distributed organizations driven by organizational entrepreneurship, many of which are based on blockchain technology. The self-organization of DAO members and their entrepreneurial behaviour are crucial to the organization's development. Research on entrepreneurial behaviour in DAOs is scarce. Cryptocurrency markets, blockchain technologies, and community sentiment can evolve rapidly, making it important to longitudinally research such organizations and the entrepreneurship among their members. Research Design & Methods: We formulated research propositions and combined qualitative and longitudinal interviews with entrepreneurially active members of a DAO with data science-based sentiment analysis of the main Nano community over the course of 16 months. Findings: The entrepreneurial behaviour of DAO members can hinge on external circumstances, such as the health of the overall cryptocurrency market. Partly resulting from a crypto downturn, some of Nano's entrepreneurially active members reduced their engagement and stopped or downsized their conduction of entrepreneurial tasks. This change was also linked to lower levels of community activity and deteriorating sentiment scores. Entrepreneurial tasks such as marketing or outreach to customers were conducted to a lesser extent. The resulting picture is one of a fluid state of entrepreneurship within this DAO. We also found internal factors influencing entrepreneurial behaviour, especially related to the distinction between technology-oriented and market-oriented members and their changing levels of activity. Implications & Recommendations: The findings highlight the influence of external factors - such as the health of the cryptocurrency market - on the entrepreneurial behaviour of DAO members. This suggests that the success and engagement of entrepreneurial individuals within a DAO can be subject to volatility and fluctuations in the broader market, emphasizing the need for adaptability and resilience. Contribution & Value Added: This is one of the first articles to address the connection between entrepreneurship and DAOs based on blockchain. In doing so, it benefits from a unique data set comprising quantitative and qualitative elements.
Keywords: L26; G32; D85; 330; blockchain; decentralized autonomous organization; entrepreneurship; financial technology; entrepreneurial behaviour; financial markets